Influence of Modern Technologies on the Formation of Cultivated Cherry Varieties, in Temperate Climates - Mamalova Kh. E. (BIO Web of Conferences, 2023)
The present article is devoted to the study of foreign cherry varieties on different rootstocks. Of all stone fruit crops, the most common is cherry. Cherry fruits are particularly valuable products, which have not only nutritional but also medicinal properties. The diversity of cherry varieties, determined by their morphological features, used as a means of production in certain natural and economic conditions. In this connection, in the ecological zone of our region, a comprehensive assessment of the biological features of different varieties of cherry trees of world selection is given. The influence of modern technologies on the formation of the crown and fruit, as well as the condition of the seedling as a whole, has been studied. The value of the studied traits lies in the characterization of biometric indicators affecting the aboveground elements of fruit trees and the general economic evaluation of cultivated varieties of sweet cherry, in temperate climatic conditions.